2010
DOI: 10.1016/j.compstruc.2010.02.010
|View full text |Cite
|
Sign up to set email alerts
|

Convergence acceleration using the residual shape technique when solving structure–acoustic coupling with the Patch Transfer Functions method

Abstract: The forced response of the structure-water-filled cavity system is investigated from the Patch Transfer Functions method. In such a case, a poor convergence of the PTF method is observed when using standard mode expansion to build the cavity-PTF. To improve its convergence and maintain the advantages of substructuring, residual shapes are introduced in the cavity-PTF computation, which is the new material of this article. This technique is successfully applied on numerical examples, highlighting the interest o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 21 publications
(27 reference statements)
0
24
0
Order By: Relevance
“…2 have been formulated accordingly, which include flexible plate mobility Y p (Appendix A), equivalent aperture mobility Y a [Eq. (8)], and MPP mobility Y mpp [Eq. (13)].…”
Section: Formulationmentioning
confidence: 99%
“…2 have been formulated accordingly, which include flexible plate mobility Y p (Appendix A), equivalent aperture mobility Y a [Eq. (8)], and MPP mobility Y mpp [Eq. (13)].…”
Section: Formulationmentioning
confidence: 99%
“…Writing the continuity conditions at the coupling interface allows us to assemble the two parts. The particularity of the present model compared to [17,18] is that the fluid added mass effect is taken into account through the "wet modal frequencies" (which are estimated by assuming the fluid incompressible) instead of using the imaginary part of the acoustic impedance of the fluid domain. This permits to overcome the convergence issue evoked in [18] concerning the patch size criterion.…”
Section: Preamble: Calculation Of Frequency Response Functionsmentioning
confidence: 99%
“…In the approach proposed, the PAI of the structure-cavity subsystem are derived from its FE model. At a given angular frequency ω, the classical (U,P) formulation of this subsystem is written as follows: (see [20,21]) :…”
Section: Formulationmentioning
confidence: 99%
“…This approach is not based on an assumption of weak coupling between subsystems, thus it can be used to solve problems of fluid-structure interaction in heavy fluid. Initial developments [20] based on partitioning at the fluid-structure interface have shown that using a standard mode expansion to build the cavity-PTF leads to poor convergence of the PTF method in heavy fluid (as opposed to light fluid). To overcome this problem, the residual shape concept was introduced in the cavity-PTF calculation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation